A practical physical-layer security method for precoded OSTBC-based systems - Hamamreh, Jehad M.; Güvenkaya, Ertu?rul; Baykaş, Tunçer; Arslan, Hüseyin (Institute of Electrical and Electronics Engineers, 2016)
In this work, we investigate the security performance obtained by employing a practical precoded orthogonal space time block coding method (POSTBC) in MISO wireless networks. In particular, space time codewords are precoded with an optimum matrix that minimizes the error rate at only the legitimate user (Bob). The acquired results depict that there exists a security gap region in the resulting BER performance as a consequence of using POSTBC. Moreover, we enhance the performance more by developing a new hybrid and green security method called precoding along with partial pre-equalizing (PCPPE). In this method, the transmitted symbols are precoded by a new precoder composed of both the original precoder and a new designed unitary matrix that maps Bob's channel amplitudes or phases estimated over the transmitting antennas into 2D orthonormal matrix. Additionally, three issues associated with the proposed security method have been tackled. Including: The slight increase in the transmit power, the appropriate selection process of the optimal precoding matrix, and the effect of imperfect channel estimation and reciprocity. The comparative simulation results prove that PCPPE method provides a secure link among the legitimate parties without sacrificing Bob's reliability although an eavesdropper is assumed to be fully aware of the used method and the original selected precoding matrix indicator (PMI).
Keywords: Practical; Physical-Layer; Security Method